P03.02.B Vestibular side effects following robotic guided stereotactic radiosurgery of vestibular schwannoma. (5th September 2022) - Rueß, D; Pöhlmann, L; Jünger, S; Kocher, M; Ruge, M
Abstract: Background: New-onset vestibular disorders (VD), such as dizziness and imbalance, are common side effects after stereotactic radiosurgery (SRS) for vestibular schwannomas (VS). Although these symptoms can severely affect the daily life of VS patients, there are limited data available providing prognostic information on the risk of developing VD after SRS. Material and Methods: We included patients who received Cyberknife® SRS for newly diagnosed unilateral VS between 2012 and 2015. The incidence of vestibular disorders before and after treatment was recorded and correlated with tumor, patient, and treatment characteristics. Results: We identified 71 patients with a median age of 58 years (range: 21-82) and a median follow-up of 66 months (range: 3-105). Tumor volume before treatment was 1.5 cm 3 ± 1.4 (range: 0.1-8.6). A mean marginal dose of 12.9 Gy ± 0.3 (range: 12-14) was administered, and all studied patients remained free of tumor recurrence. Forty-one (58%) of the patients had VD prior to SRS. Of the remaining 30 patients who did not have VD before treatment, 16 (53%) developed new VD (vertigo, n=4; balance disorders, n=8; mixture of VD, n=4). The median time to onset of symptoms was 6 months (range: 2-36). In most patients (n=11, 69%), the new symptoms completely resolved within a median time of 21 months (range: 1-63). In multivariate analysis, neither tumor volume (p=0.7), age (p=0.06), nor radiation dose (p=0.16) were significantly associated with the occurrence of VD. Conclusion: In this cohort, about half of the patients develop new onset of transient VD after SRS. The incidence of VD after SRS was found to be independent from usual tumor-, patient- and treatment-related factors. Therefore, a detailed analysis of the dose exposure to the structures of the vestibular apparatus is recommended.